2019
DOI: 10.1039/c9ra05117a
|View full text |Cite
|
Sign up to set email alerts
|

X-ray powder diffraction to analyse bimetallic core–shell nanoparticles (gold and palladium; 7–8 nm)

Abstract: A comparative X-ray powder diffraction study on poly(N-vinyl pyrrolidone) (PVP)-stabilized palladium and gold nanoparticles and bimetallic Pd–Au nanoparticles (both types of core–shell nanostructures) was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Figure shows XRD patterns of the Pd@Ru cubic nanocrystals, indicating that the Ru shells took an fcc structure regardless of the template size. , In all cases, the main XRD peak was located around 40.2°, which is between the reference peaks of fcc-Pd and fcc-Ru. For core–shell nanocrystals, we do not expect to observe separate XRD peaks with strong intensities for the core and the shell. ,,, Especially in the case where Pd and Ru adopt the same crystal phase, the observed peaks should be an average of the peaks corresponding to the core and the shell, with relative contributions depending on the shell thickness, particle size, and orientation. , In contrast, a minor separation, expressed by the presence of secondary peaks or small shoulders next to the main peaks, is expected when the core and the shell have different crystal structures. This shoulder peak arising from the core tended to vary in intensity depending on the thickness and crystal phase of the shell, the particle size, and the overall contribution of each phase to the entire sample. ,, As such, we consider the position of the main peak with the strongest intensity as the most important feature to identify the phase of the shell.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Figure shows XRD patterns of the Pd@Ru cubic nanocrystals, indicating that the Ru shells took an fcc structure regardless of the template size. , In all cases, the main XRD peak was located around 40.2°, which is between the reference peaks of fcc-Pd and fcc-Ru. For core–shell nanocrystals, we do not expect to observe separate XRD peaks with strong intensities for the core and the shell. ,,, Especially in the case where Pd and Ru adopt the same crystal phase, the observed peaks should be an average of the peaks corresponding to the core and the shell, with relative contributions depending on the shell thickness, particle size, and orientation. , In contrast, a minor separation, expressed by the presence of secondary peaks or small shoulders next to the main peaks, is expected when the core and the shell have different crystal structures. This shoulder peak arising from the core tended to vary in intensity depending on the thickness and crystal phase of the shell, the particle size, and the overall contribution of each phase to the entire sample. ,, As such, we consider the position of the main peak with the strongest intensity as the most important feature to identify the phase of the shell.…”
Section: Resultsmentioning
confidence: 85%
“…Additionally, all peaks were shifted to smaller angles compared to the reference peaks of fcc-Ru due to the tensile strain in the Ru{100} overlayers deposited on Pd{100} facets . Notably, the lack of a well-resolved peak corresponding to the hcp - Ru phase indicates that the Ru shells were entirely composed of fcc-Ru. , Taken together, it can be concluded that the inherent mismatch between the {100} facets of the fcc lattice and the facets of an hcp lattice forces the Ru overlayers on cubic templates into the metastable fcc phase …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Characteristic lattice fringes are observed in Figure 6 with a d -spacing of 2.37 Å, which is assigned to {111} lattice space of metallic gold [7], indicating the large exposed area of the corresponding facet. 7), indexed to {111}, {200}, and {220} lattice planes of the face-centered cubic (fcc) structure of gold with the Joint Committee on Powder Diffraction Standard (JCPDS) card number 00-004-084 [31,32]. Among all, the highest diffraction peak is observed at 38.2 °, corresponding to the {111} lattice plane, attributed to the preferential growth of AuNSs along the {111} plane.…”
Section: Influence Of Collagen Concentrationmentioning
confidence: 99%